THE ROLE OF MEDICAL SECRETARY IN MEDICAL RECORDS AND REPORTS: A COMPREHENSIVE REVIEW - Abdullah Khaled Alqahtani, Majed Ali Ahmed Nasseri, ‏mahir Hasan Muhamad ‏Alealaasi, Rajeh Abdullah Ayed Al-awfi, Humoud Faraj Alqahtani, Waleed Ibrahim Aldayel, Talal Awadh Alsulays, Reem Abdullah Saeed Asseri,; Mohammed Ibrahim Al Tamimi, Khalid Mohammad Alaskar, Bader Saad Ali Altamimi, Abdullateef Saleem Aljihni, Ali Sulaiman Altamimi, Adel Mohammed Alzaidi, Khalid Abdullah Altamimi (Chelonian Research Foundation, 2022)
Medical secretaries' roles and responsibilities have been impacted dramatically by the integration of Electronic Health Records (EHRs) into healthcare settings. This study, carried out at Regional Hospital in Denmark, uses qualitative and quantitative studies in both the endocrinology and emergency departments to investigate how the installation of EHRs has affected medical secretarial work. The findings point to possible advantages like reduced administrative procedures and better data quality, which would raise total healthcare delivery efficiency. But there are drawbacks as well, such the requirement for thorough training and process modification. To overcome these obstacles and maximize the utilization of EHR systems, cooperation between IT specialists, administrators, and healthcare practitioners is essential. The results highlight the significance of taking departmental contexts into account and offering medical secretaries sufficient support throughout the EHR transition, with the ultimate goal being to optimize the advantages and get beyond any potential roadblocks related to EHR integration in healthcare settings. Keywords: Medical Records, Electronic Records, Medical Secretary, Health reports.